PENGARUH PENERAPAN GOOD CORPORATE GOVERNANCE DAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY PADA NILAI PERUSAHAAN - Inastri, Mirsha Amirah; Mimba, Ni Putu Sri Harta (E-Jurnal Akuntansi; Vol 21 No 2 (2017), 2017)
Every company aims to increasethe the firm value, but not all companies can fulfill it. It is because the parties involved in the company sometimes have conflict with each other, so the company's goals difficult to achieve. This conflict can be solved with good corporate governance (GCG). The implementation of GCG must meet five principles, one of them which is accountability. Accountability can be done through the disclosure on Corporate Social Responsibility (CSR) in sustainability report. This study aims to determine the effect of GCG implementation and CSR disclosure on corporate value. The number of research samples is 33 company data from 16 companies. This research uses purposive sampling sampling method with the following criteria; listed companies in Indonesia Stock Exchange, included the CGPI rating (Corporate Governance Perception Index), and disclose sustainability report as per GRI G-4 for the period from 2013 untill 2016. The analysis technique used is multiple linear regression analysis. This study has two results; firstly, GCG implementation variables proxied by CGPI score have positive and significant effect on firm value because test significance value t equal to 0,011 less than level of significance 0,05. Secondly, CSR disclosure variables proxied by CSRI (Corporate Social Responsibility Index) have no positive and insignificant effect on firm value because the significance value of t test is 0.710 greater than the 0.05 level of significance.